2021
DOI: 10.1021/acssuschemeng.0c08653
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Interactions between Azole-Anion-Based Ionic Liquids and Propargylic Alcohol: Influence on the Carboxylative Cyclization of Propargylic Alcohol with Carbon Dioxide

Abstract: To reveal the interactions between azole-anionbased ionic liquids (AILs) and propargyl alcohol (PA) and their effect on the carboxylative cyclization reaction of PA with CO 2 , three AILs, namely, [P 66614 ][Im], [P 66614 ][4-MeIm], and [P 66614 ][4-BrIm], were synthesized and characterized. The interactions between the AILs with 2-methyl-3-butyn-2-ol (MBY) were investigated through IR and 1 H NMR spectra and DFT calculations. The results indicate that azole-based anions can form H-bonds with the hydroxyl (O−H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 65 publications
(105 reference statements)
3
11
0
Order By: Relevance
“…Combined with the results of this study and our previous report, 10 it can be reasonably suggested that both anions and cations of AILs play an important role in activating MBY during the AIL-promoted carboxylative cyclization of MBY with CO 2 .…”
Section: The Effect Of the Interactions Between Ails And Mby On The A...supporting
confidence: 88%
See 4 more Smart Citations
“…Combined with the results of this study and our previous report, 10 it can be reasonably suggested that both anions and cations of AILs play an important role in activating MBY during the AIL-promoted carboxylative cyclization of MBY with CO 2 .…”
Section: The Effect Of the Interactions Between Ails And Mby On The A...supporting
confidence: 88%
“…[53][54][55] Therefore, d of the alkyl groups of [P 66614 ] + of AILs + MBY mixtures as a function of x AIL are investigated, which have been reported in our previous work, but not focused on and discussed. 10 The results show that d of the terminal CH 3 and the adjacent CH 2 are almost unchanged with the increasing of x AIL (the variation range is within 0.005 ppm, which is close to the measurement accuracy 56 ), indicating that their electron density remains unchanged, which is attributed to these groups being far away from the positive and negative charge centers, and there are no obvious group crossover and charge overlap between them as x AIL increases. As illustrated in Fig.…”
Section: Viscosity and 1 H Nmr Chemical Shifts Of Ails + Mby And CCL ...supporting
confidence: 65%
See 3 more Smart Citations